Source Estimate for the 1960 Chile Earthquake From Joint Inversion of Geodetic and Transoceanic Tsunami Data. Issue 3 (14th March 2019) - Ho, Tung‐Cheng; Satake, Kenji; Watada, Shingo; Fujii, Yushiro
Abstract: The slip distribution of the 1960 Chile earthquake was estimated using geodetic data, local tsunami data, and newly usable transoceanic tsunami data. The large slips triggered a significant tsunami which was recorded by the tide gauges around the Pacific Ocean. We performed a two‐step inversion to estimate the slip distribution. In the first step, we jointly inverted the tsunami waveforms and local geodetic data to recover the ground and seafloor vertical displacement. The transoceanic tsunami data could not be used for waveform inversions until the wave phase and arrival time discrepancies were recently reconciled by improving the long‐wave theory with the phase correction method. The random arrival time discrepancy due to inaccurate local bathymetry and/or instrumental problems was considered by the optimal time alignment. In the second step, we estimated the slip distribution on the plate interface by inverting the vertical displacement obtained in the first step. Checkerboard tests showed that our method and data can resolve displacement at a spatial resolution of at least 100 km but cannot estimate the rupture velocity. The result for actual data shows a rupture extended about 800 km with a width of about 150 km and three asperities. The large slips are concentrated in the offshore shallow plate interface. Our results indicate that the central and south patches contribute to the large coastal elevation changes at southern source area and high tsunami waves at far field. The estimated moment ranges 1.3–1.9 × 10 23 Nm ( Mw 9.3–9.4) for rake angles of 90–140°. Key Points: The slip distribution of the 1960 Chile earthquake is estimated from transoceanic tsunami data, local tsunami data, and geodetic data The seismic moment is 1.4 x 10 23 Nm ( Mw 9.4) for rake angle of 110°, and the slip consists of three shallow asperities Large central and south asperities are required to reconstruct the southern high coastal uplift and large tsunami waves at far field